Efektivitas Model Pelatihan Keterampilan berbasis Usaha Pertanian-Peternakan Terpadu Pasca Bencana Erupsi Gunung Merapi di Kecamatan Selo, Kabupaten Boyolali - Shanti Emawati; Lutojo Lutojo; Heru Irianto; Endang Tri Rahayu; Ayu Intan Sari (Universitas Sebelas Maret (UNS), 2012)
The purpose of this study was to determine the effectiveness of skills training model based integrated crop-livestock system in Selo, Boyolali. This research method using the approach of Research and Development with data collection techniques of observation, documentation and interviews. Test of training model using Pre-Experimental Design with One Group Pretest-Posttest Design. Data were analyzed using the nonparametric statistical analysis Wilcoxon Match Pairs Test. The test results obtained significant improvement of cognitive, psychomotor and affective. The resultsshowed that based on analysis using Wilcoxon test by comparing the results of pretest and posttest on all three aspects: knowledge, skills and attitudes showed significant results, this means there is a change or an increase in the ability of the participants after being given skills training so that it can be concluded that the skills training of integrated crop-livestock system in Selo, Boyolali effectively empower farmers.Keywords: model of skills training, integrated crop-livestock system, post-eruption of Mount Merapi, empowerment, socio-economic recovery